Properties of Oil Palm Empty Fruit Bunch-Filled Recycled Acrylonitrile Butadiene Styrene Composites: Effect of Shapes and Filler Loadings with Random Orientation - Siti Nikmatin; Achmad Syafiuddin; Dwi Arso Yedi Irwanto (BioResources, 2016)
Exploration of natural resources as composite fillers is still under intensive investigation. Previous works mention that nano-size natural fillers provide an alternative solution to improve certain composite properties compared with macro- and micro-size nanofibers. This work prepared biocomposites formulated from recycled acrylonitrile butadiene styrene (ABS) reinforced by nano powders or long fibers of oil palm empty fruit bunch (OPEFB). Composite properties in terms of density, Fourier transform infrared spectroscopy, surface morphology, melt flow rate, tensile strength, impact strength, and hardness were studied. The density of all composites generally increased with increasing filler loading. Composites with nano powder fillers had lesser voids than those composites with the long fiber. Melt flow rate of all composites fluctuated with filler loadings. Increasing filler loadings for composites with long fiber increased brittleness. By contrast, composites with nano powder fillers were more elastic at the higher filler loading. It was confirmed that impact and hardness properties of the composites with nano powder fillers increased with increasing filler loading. Moreover, composites with long fiber fillers decreased their impact and hardness properties with filler loadings increase.